A New Formula For Rate Of Swelling Of Expansive Clay Soils - Muntohar, Agus Setyo; Hashim, Roslan (Jurnal Semesta Teknika, 2005)
The study of engineered expansive soils attracts the attention of researchers since this soil is mixed and increasingly used in many geotechnical and geoenvironmental application. This paper attempts to the study of swelling properties i.e. swell and swelling pressure, rate of swell, and water adsorption during swell. The kaolin-bentonite mix and sand-bentonite mix specimens are statically compacted and tested in conventional oedometer apparatus for swelling determination. The results of the study show that the mechanism of swell follows three distinct stages: intervoid, primary, and secondary swelling. The swell occurs since the soils adsorb water during water uptake. The rate of swell and maximum swelling are successfully determined using hyperbolic equation.